Uptake of the MedsCheck annual medication review service in Ontario community pharmacies between 2007 and 2013 - Dolovich, Lisa (Can Pharm J (Ott), 2016)
BACKGROUND: MedsCheck Annual (MCA) is an Ontario government-funded medication review service for individuals taking 3 or more prescription medications for chronic conditions. METHODS: This cohort study analyzed linked administrative claims data from April 1, 2007, to March 31, 2013. Trends in MCA claims and recipient characteristics were examined. RESULTS: A total of 1,498,440 Ontarians (55% seniors, 55% female) received an MCA. One-third (36%) had 2 or more MCAs within 6 years. Service provision increased over time, with a sharper increase from 2010 onward. Almost half of Ontario pharmacies made at least 1 MCA claim in the first month of the program. Hypertension, respiratory disease, diabetes, psychiatric conditions and arthritis were common comorbidities. Recipients older than 65 years were most commonly dispensed an antihypertensive and/or antihyperlipidemic drug in the prior year and received an average of 11 unique prescription medications. Thirty-eight percent of recipients visited an emergency department or were hospitalized in the year prior to their first MCA. DISCUSSION: Over the first 6 years of the program, approximately 1 in 9 Ontarians received an MCA. There was rapid and widespread uptake of the service. Common chronic conditions were well represented among MCA recipients. Older MCA recipients had less emergency department use compared with population-based estimates. CONCLUSIONS: Medication reviews increased over time; however, the number of persons receiving the service more than once was low. Service delivery was generally consistent with program eligibility; however, there are some findings possibly consistent with delivery to less complex patients.